Use of the pictet-spengler reaction for the synthesis of 1,4-disubstituted-1,2,3,4-tetrahydro-beta-carbolines and 1,4-disubstituted-beta-carbolines: formation of gamma-carbolines - Kusurkar, Radhika S.; Alkobati, Nabil A. H.; Gokule, Anita S.; Puranik, Vedavati G. (Tetrahedron, 2008)
Microwave-assisted conjugate addition of indole on nitro-olefins furnished nitro compounds, which were reduced to tryptamines. Further, by using Pictet-Spengler condensation, new 1,4-disubstituted-1,2,3,4-tetrahydro-beta-carbolines were synthesized in diastereoselective manner. Dehydrogenation of the tetrahydro-beta-carbolines produced new 1,4-disubstituted-beta-carbolines. As a new observation, in some of the cases, Pictet-Spengler condensation and dehydrogenation gave two products, namely 1,4-disubstituted-beta-carbolines and 1,4-disubstituted-gamma-carbolines. A mechanism is proposed for this observation. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3; 4-Disubstituted-1; 4-disubstituted-beta-carboline; 4-disubstituted-gamma-carboline; 4-tetrahydro-beta-carboline; 4-tetrahydro-gamma-carboline; Pictet-Spengler reaction

Unexpected observations during the total synthesis of calothrixin B-sodium methoxide as a source of hydride - Bhosale, Shrikar M.; Momin, Aadil A.; Kunjir, Shrikant; Rajamohanan, P. R.; Kusurkar, Radhika S. (Tetrahedron Letters, 2014)
During the total synthesis of calothrixin B, various novel and unexpected results were noticed such as cleavage of C-N bond in imine using sodium cyanoborohydride, sodium methoxide as a hydride source for reduction, deformylation in the presence of bromine, and deacylation using ceric ammonium nitrate (CAN). A detailed mechanism has been proposed for the unexpected results and a few of them are generalized. Temperature dependent NMR studies have been carried out for confirmation of the structure of one of the intermediates in the synthetic sequence. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Azoxybenzene; Calothrixin B; reduction; Sodium cyanoborohydride; Sodium methoxide